TRANSFORMASI DIGITAL DAN FINANCIAL TECHNOLOGY TERHADAP PENINGKATAN PENDAPATAN UMKM DIMASA PANDEMI COVID-19 DI KABUPATEN PASURUAN: Transformasi Digital, Financial Technology, Peningkatan Pendapatan UMKM - Asadi, Asadi; Sularsih, Hermi (Jurnal Paradigma Ekonomika, 2022)
This research aims to determine the effect of Digital Transformation and Financial Technology on Increasing MSME Income during the Covid-19 Pandemic in Pasuruan Regency. This type of research is a type of quantitative research with a set sample of 400 respondents. Multiple regression analysis test using SPSS. The results of the study show that the Digital Transformation and Financial Technology variables significantly have a positive effect on increasing MSME income during the Covid-19 pandemic.